Prenatal alcohol exposure-related reading and phonological processing deficits mediated by working memory - Meiring, Landi-Chantel (Department of Psychology, 2018)
Few research studies have investigated the effects of prenatal alcohol exposure (PAE) on reading ability and/or on phonological processing. Most published studies have only included measures of single-word reading. This choice means those studies may lack ecological validity in that they might not have adequately captured the real-life reading difficulties experienced by individuals with PAE. Furthermore, only a handful have considered the possible mediating roles of those higher-order cognitive functions (e.g., working memory (WM)) that are known to be affected by PAE. The current research employed an extensive battery of phonological processing measures, as well as a reading test that featured measures of reading accuracy, reading rate, and comprehension. A sample of 159 children between 9 and 14 years of age, with varying degrees of PAE, including heavily exposed children and non- or minimally-exposed controls, were tested. The design also considered the potential for a mediating role of WM on performances on these tests. Overall, results showed performance deficits in children with either fetal alcohol syndrome or partial fetal alcohol syndrome on reading comprehension and on four measures of phonological processing, after control for potential confounders. Additional analyses showed that performance within all five of these reading-related domains were at least partially mediated by WM performance. I discuss these results in the context of previous findings in this literature, and describe their implications for reading interventions in children and adolescents with PAE.